👤
a fost răspuns

3 Calculati:
a (-6-4)-(-10 + 8) + (-2+9):
b 1-6-(-9+2)+(-5+8)]-[-2 +6-(-6+8)].​


3 Calculatia 6410 8 29b 1692582 668 class=

Răspuns :

Răspuns:

a. - 1

b. 2

Explicație pas cu pas:

a.  

( - 6 - 4 ) - ( - 10 + 8 ) + ( - 2 + 9 ) = - 1  

- 10 - ( - 2 ) + ( 7 ) = - 1  

- 10 + 2 + 7 = - 1  

- 8 + 7 = - 1

b.  

[ - 6 - ( - 9 + 2 ) + ( - 5 + 8 ) ] - [ - 2 + 6 - ( - 6 + 8 ) ] = 2  

[ - 6 - ( - 7 ) + ( 3 ) ] - [ - 2 + 6 - ( 2 ) ] = 2  

[ - 6 + 7 + 3 ] - [ - 2 + 6 - 2 ] = 2  

[ 1 + 3 ] - [ 4 - 2 ] = 2  

4 - 2 = 2.